Pengetahuan dan Perilaku Mahasiswa Kedokteran di Sebuah Universitas di Jakarta tentang Penggunaan dan Perawatan Lensa Kontak - Sri Wahdini; Anita D. Shanti; Hans M. Sinaga (Fakultas Kedokteran Universitas Riau, 2019)
Knowledge and behaviour about properly handle and maintain contact lens is essential to prevent infection. The purpose of this study was to determine the knowledge and behaviour of medical students in one of university in Jakarta about the use and care of contact lens in contact lenses users. This study uses cross-sectional design. Data was collected in January-June 2015 in one of university in Jakarta using specific questionnaire containing 10 questions. Respondents were the students in the first, second, and third years who use the contact lens. There were 97 respondents and the percentage of respondent with good, fair, and poor knowledge level about the use and care of contact lens were 40 (41.2%), 29 (29.9%), and 28 (28.9%). The number of respondents with good, fair, and poor behavior level about the care of contact lens were 63 (64.9%), 31 (32.0%), and 3 (3.1%). The knowledge and behaviour among medical students wearing contact lenses about the use and care of contact lens were in good level.